The method of collective variables: a link with the density functional theory - Patsahan, O.; Mryglod, I. (Condensed Matter Physics, 2012)
Recently, based on the method of collective variables the statistical field theory for multicomponent inhomogeneous systems was formulated [O. Patsahan, I. Mryglod, J.-M. Caillol, Journal of Physical Studies, 2007, 11, 133]. In this letter we establish a link between this approach and the classical density functional theory for inhomogeneous fluids. Недавно, використовуючи метод колективних змiнних, було сформульовано статистико-польову теорiю для багатокомпонентних неоднорiдних систем [O. Patsahan, I. Mryglod, J.-M. Caillol, Journal of Physical Studi-es, 2007, 11, 133]. В цьому повiдомленнi ми встановлюємо зв’язок мiж цим пiдходом i класичною теорiю функцiоналу густини для неоднорiдних плинiв.